A COMPARATIVE STUDY ON GROWTH, CARCASS TRAITS AND BODY COMPOSITION OF AWASSI AND KARADI LAMBS RAISED UNDER TWO LEVELS OF FEEDING AND SLAUGHTERED AT DIFFERENT WEIGHTS: 1- GROWTH PERFORMANCE AND CARCASS TRAITS - Al-Sherwany, D. A. O.; Alkass, J. E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Sixteen weaned (3.5-4 months) entire male lambs from each of Awassi and Karadi were weighed and randomly divided equally into two groups to receive concentrate (16% crude protein and 2769 kcal energy) either ad libitum or 3% of their body weights, and to be slaughtered at 36 or 44 kg. Results revealed that overall means of daily gain in weight, dressing percentage based on slaughter and empty body weight, rib eye area and fat thickness were 0.258±0.01 kg, 46.54± 0.49%, 54.35 ± 0.40%, 14.98 ±0.44 cm2 and 2.86 ± 0.12 mm, respectively. It seems that Awassi lambs significantly surpass Karadi lambs in dressing percentage based on slaughter weight and had thicker subcutaneous fat, only. Also, lambs fed ad lib excell significantly those lambs fed 3% in daily gain in weight, dressing percentage based on slaughter weight, and fat thickness. Lambs slaughtered at 44 kg had significantly higher dressing percentage, rib eye area and fat thickness.